Unity power factor operation and neutral current compensation of diesel generator set feeding three‐phase four‐wire loads. Issue 13 (1st October 2015) - Niwas, Ram; Singh, Bhim; Goel, Sagar; Jain, Chinmay
Abstract : This study deals with power quality improvement in a diesel generator (DG) set‐based standalone supply system feeding three‐phase four‐wire(3P4W) loads. The proposed system consists of a diesel engine, three‐phase wound field synchronous generator, a four‐leg voltage source converter (VSC) and3P4W loads. The four‐leg VSC with a capacitor connected on its DC link is used for neutral current compensation and unity power factor operation of the DG set. In addition, the VSC provides harmonics elimination and the load balancing. The voltage of the DG system is controlled by excitation control of the synchronous generator and the frequency is controlled by speed regulating system of the diesel engine. The speed of the engine is regulated by controlling the fuel injection of the diesel engine. An adaptive theory‐based notch filter algorithm is used to extract fundamental component of the load currents for estimation of reference source currents.